The importance of odours in the workplace: a review - Kapustová, Zuzana; Elena Horská, Elena; Berčík, Jakub; Paluchová, Johana; Gurčík, Ľubomír (Studia Mundi – Economica, 2018)
The most persistent memory on any space is often its odour, therefore the presence of a pleasant odours results in higher self efficacy, setting higher goals and employing efficient work strategies in comparison to working in a no-scent condition. Moreover, unpleasant odours might increase stress level and result in a loss of productivity. The paper aims to provide a review of the available literature regarding the influence of odours on the human activities with special reference to essential oils in the workplace and their impact on work performance.